Speech Acts in EFL Textbook: A Pragmatic Analysis - Noer Aida, Siti; Basya, Dihliza; Mahbub , Moh Arif (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2022)
This content analysis study aimed to identify speech act in Indonesian EFL Textbookentitled Think Globally Act Locallypublished by the Ministry of Education and Culture (MONEC) in 2018. The procedure of analyzing the data are, read and reread the textbook, identifying the forms of speech acts in EFL textbook, coding, the researcher classifying relevant data representing illocutionary, tabulating the frequency and percentage of each speech act, describing and interpreting the data in order to address the statement of problem.Drawing upon the Searle’s (1977) categories, I found 52 kinds of speech act categorized as Illocutionary act; representative, commissive, directive, expressive, and declarative. Based on the research findings, it can be concluded that textbook representedvarious speech acts that could help learnersin their EFL learning.